Human Development and Trade Liberalization A Comparative Study of Developing versus Developed Economies (Economic Journal of Nepal, 2015)
The aim of this paper is a comparative study of developing versus developed countries regarding the relationship between human development and trade liberalization. Human development index is used as a measure of development (social development) it is a combined or composite measure of three main components which are education, healthy life, and a decent standard of living. For this purpose, we selected seven developing and seven developed countries and use the log form of trade openness (trade liberalization), HDI, population growth, economic growth (GDP) and inflation (CPI) for the period 2005-2012. Results of fixed effect technique reveal a positive and significant link of human development with trade liberalization and GDP and negative and significant effect of population growth for both sets of countries, while inflation has negative and significant effect on developed countries and showing insignificant effect on developing countries. These results showed that trade openness have same effects for both sets of countries.